Effects of Mesophilic and Thermophilic Temperature Condition to Biogas Production (Methane) from Palm Oil Mill Effluent (POME) with Cow Manures - Muhammad Fajar Fajar; Muhammad Faizal; Novia Novia (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2018)
Biogas is an environmentally friendly renewable energy source. Biogas can be used using Palm Oil Mill Effluents (POME). However, the % yield of biogas productivity is still not optimum due to the low conversion. The biogas productivity can be optimized by adding methanogen bacteria which increase the methane production through the anaerobic fermentation process. This study aims to utilize cow manures as the source of methanogen bacteria in methane production from POME. Furthermore, this study specifically aims to obtain the optimum productivity condition of biogas production by the composition ratio of POME and cow manures to the amount of fermentation time at 35oC and 50oC for mesophilic and thermophilic bacteria, respectively. The ratio of POME and cow mature were A1 (100:0), A2 (80:20), A3 (70:30), A4 (60:40), and A5 (0:100). The highest yield of biogas production was A2 ratio using the thermophilic condition which showed 51.33% mol with the total solid decline of 73.43%, COD removal of 77.01%, and BOD removal of 70.02%.